Optimization of Factors Influencing Agrobacterium mediated Genetic Transformation in Eclipta alba (L.) Hassk. - Bardar, Shruti; Kothari, SL; Kachhwaha, Sumita (Plant Tissue Culture and Biotechnology, 2016)
An efficient and reproducible protocol for in vitro plant regeneration and Agrobacterium-mediated genetic transformation was developed for Eclipta alba (L.) Hassk. using nodal explants. Several parameters affecting Agrobacteriummediated gene delivery were investigated and optimized. These include antibiotic concentration, preculture period, infection time, use of acetosyringone, co-cultivation period and temperature and increased level of copper in induction, co-cultivation and regeneration medium. Incorporation of elevated level of CuSO4 led to significant improvements in plant regeneration and recovery of transformed plants. The highest frequency of transformation was observed when explants were infected and co-cultivated at 23oC. Higher transformation frequency was attained by augmenting the medium with 1.0 ?M CuSO4 which was ten times the normal MS level. Addition of acetosyringone in the infection and co-cultivation media was very beneficial and resulted in greater transformation efficiency. Transient and stable expression of gus gene was confirmed with histochemical assay of infected explants and leaves of regenerated transformants, respectively. Molecular analysis of transformed plants with nptII and gus A specific primers revealed the amplification of nptII and gus gene thereby demonstrated the efficacy of optimized protocol for A. tumefaciens-mediated genetic transformation in Eclipta alba for the first time. Plant Tissue Cult. & Biotech. 25(2): 155-164, 2015 (December)